ANALISA KOMPARATIF USAHATANI PADI ANTARA PENYIANGAN MANUAL DAN PENYIANGAN KIMIAWI (Studi Kasus Di Dsa Tanjung Kamal, Kecamatan Mangaran, Kabupaten Situbondo) - Lukman Hakim; Andina Mayangsari (Program Studi Agribisnis Fakultas Pertanian, 2015)
Research purpose is to determine whether there are differences in rice production between manual weeding and chemical weeding, to determine differences in income between manual weeding and chemical weeding, and to determine the efficiency difference between manual weeding and chemical weeding. Method of determining the area of research is purposive method. Respondent committed intentionally that taking 20 farmers weeding users manually using random sampling techniques (random), and 20 farmers using chemical weeding user survey. Respondent is intended that the same sample, with a total of 40 respondents farmers. Data analysis method used is the (t test) to test the first hypothesis there is a difference between the rice production using manually weeding and using chemical weeding. To test the second hypothesis using the (t test) there is a difference between the revenue using manually weeding and using chemical weeding. And the R/C ratio for the third hypothesis test there is a difference between the efficiency of using manually weeding and chemical weeding. The results showed there are differences in production, income and efficiency of rice significantly between using a manually weeding and using chemical weeding.